Prolonged Survival of Pig Skin on Baboons After Administration of Pig Cells Expressing Human CD47. Issue 2 (February 2017) - Tena, Aseda A.; Sachs, David H.; Mallard, Christopher; Yang, Yong-Guang; Tasaki, Masayuki; Farkash, Evan; Rosales, Ivy A.; Colvin, Robert B.; Leonard, David A.; Hawley, Robert J.
Abstract : Background: Successful xenotransplantation will likely depend, in part, on the induction of immunological tolerance, because the high levels of immunosuppression otherwise required would likely have unacceptable side effects. Rapid clearance of administered porcine hematopoietic stem cells by primate macrophages has hampered previous attempts to induce tolerance through mixed hematopoietic chimerism across a pig-to-primate barrier. Phagocytosis is normally inhibited by binding of cell surface protein CD47 to macrophage signal regulatory protein α receptors. However, pig CD47 has previously been shown to be ineffective in transducing signals through primate signal regulatory protein α. Methods: Mobilized peripheral blood hematopoietic cells from transgenic swine expressing high or low levels of human CD47 were infused into conditioned baboons at 3 time points over a 9-week period. Xenogeneic peripheral blood chimerism was assessed after each infusion. Split thickness skin grafts from the hematopoietic cell donor swine were placed on recipients 5 weeks after the last cell infusion and 7 weeks after the discontinuation of all immunosuppression to test immune response. Results: The level and duration of transient chimerism were substantially greater in baboons receiving hematopoietic cells from a pig expressing high levels of human CD47. Skin graft survival on high CD47 recipients was prolonged as well, in 1 case showing no signs of rejection at least 53 days after placement. Conclusions: Prolongation of transient porcine chimerism via transgenic expression of human CD47 in a primate model is associated with an immune modulating effect, leading to markedly prolonged survival of donor swine skin xenografts that may be applicable to clinical solid organ xenotransplantation. Abstract : Tena et al report that the transgenic expression of human CD47 by porcine peripheral blood hematopoietic cells is able to extend the period of transient chimerism in baboons, leading to markedly prolonged survival of donor-matched skin xenografts. Supplemental digital content is available in the text.